Systematic position of copepods of the genus Achtheres (Crustacea: Copepoda: Siphonostomatoida) parasitizing perch, Perca ﬂuviatilis L., and zander, Sander lucioperca (L.). - Kempter, J., W. Piasecki, K. Wieski & B. Krawczyk (Journal of Fish Diseases, 2006)
Parasitic copepods of the genus Achtheres commonly infect perch, Perca ﬂuviatilis, and zander, Sander lucioperca, in Europe. The aim of this study was to verify the speciﬁc identity of these copepods. The parasites were examined morphologically, biometrically and genetically. Statistical processing of the biometrical data was based on both empirical measurements and transformed data related to total length and genital trunk width. Principal component analysis was applied to both sets of data. DNA of both parasite ÔformsÕ was ampliﬁed using two sets of primers (EU5.8S + EU18S and 18SF1 + 28SR) and the products were subjected to restriction fragment length polymorphism (RFLP). Morphological differences were found in the overall shape of the copepod bodies as well as in the details of the armament of some appendages. The morphometric study emphasized the importance of second maxillae and genital process as the variables most distinctly distinguishing the two ÔformsÕ. The two ÔformsÕ of Achtheres differed in the DNA sequence ampliﬁed by one set of primers. RFLP revealed even more extensive differences between these two copepods. We concluded that the copepods parasitizing perch should be referred to as Achtheres percarum von Nordmann, 1832, whereas a long-forgotten name, A. sandrae Gadd, 1901, should be applied to the copepods from zander.